2009
DOI: 10.1128/ec.00067-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flagellar Phosphoproteins from Chlamydomonas reinhardtii

Abstract: Cilia and flagella are cell organelles that are highly conserved throughout evolution. For many years, the green biflagellate alga Chlamydomonas reinhardtii has served as a model for examination of the structure and function of its flagella, which are similar to certain mammalian cilia. Proteome analysis revealed the presence of several kinases and protein phosphatases in these organelles. Reversible protein phosphorylation can control ciliary beating, motility, signaling, length, and assembly. Despite the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 64 publications
9
67
1
Order By: Relevance
“…This is in contrast to the IFT A proteins isolated from the parental strain (CC-503) that also exhibited a fairly broad sedimentation, which clearly peaked at ϳ16 S with approximately half of the IFT43 present in the 16 S fractions and the other half present near the top of the gradient. It is interesting to note that the 2 S and 16 S IFT43 ran on the SDS-PAGE as a doublet, which is consistent with a previous phosphoproteomic analysis that showed that a fraction of the flagellar form of Chlamydomonas IFT43 is phosphorylated (77). The presence of the IFT43 doublet in the ift121 mutant suggests that this phosphorylation is not dependent on the association of IFT43 with complex A.…”
Section: Heterologous Expression In Bacteria Confirms An Ift121-ift43supporting
confidence: 73%
See 1 more Smart Citation
“…This is in contrast to the IFT A proteins isolated from the parental strain (CC-503) that also exhibited a fairly broad sedimentation, which clearly peaked at ϳ16 S with approximately half of the IFT43 present in the 16 S fractions and the other half present near the top of the gradient. It is interesting to note that the 2 S and 16 S IFT43 ran on the SDS-PAGE as a doublet, which is consistent with a previous phosphoproteomic analysis that showed that a fraction of the flagellar form of Chlamydomonas IFT43 is phosphorylated (77). The presence of the IFT43 doublet in the ift121 mutant suggests that this phosphorylation is not dependent on the association of IFT43 with complex A.…”
Section: Heterologous Expression In Bacteria Confirms An Ift121-ift43supporting
confidence: 73%
“…A complete loss of an IFT A subunit, such as that observed with a murine IFT122 knock-out strain shows that the loss of the IFT A complex is likely to be embryonic lethal in humans (49,87). Based on our results and the recent mammalian IFT A studies (77), it is likely that complex A is severely disrupted in the IFT122 knock-out strain; such a disruption would explain why the cilia in these mice are considerably shorter than normal (incomplete assembly) and engorged (defective in retrograde transport). Thus, mutations resulting in more subtle phenotypes are likely required to generate disease states that allow full gestation and live birth.…”
Section: Specific Interactions Of Ift a And Formation Of Ift A Core-mentioning
confidence: 89%
“…CK1 is involved in biological processes including circadian rhythm establishment, vesicular trafficking, DNA repair, the cell cycle, and morphogenesis (Gross et al, 1995;Akashi et al, 2002;Cheong and Virshup, 2011). A number of cytoskeleton-related proteins have been identified as targets of CK1 kinases; these targets include cofilin, twinfilin, myosin, tropin, spectrin3, dynein, a-/b-tubulin, microtubuleassociated protein, and kinesin-like protein (Boesger et al, 2014;Knippschild et al, 2014;Peng et al, 2015). In addition to the other cytoskeleton-related proteins, CK1 directly phosphorylates actin protein in vitro (Shibayama et al, 1986;Knippschild et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis was done using the Proteome Discoverer software (version 1.0) from Thermo Electron including the SEQUEST algorithm (Link et al, 1999). The parameters for all database searches were set to achieve a false discovery rate of not more than 1% for each individual analysis according to Boesger et al (2009). Data were searched against the Joint Genome Institute C. reinhardtii database (versions 2.0 and 4.0).…”
Section: Peptide Identification By Nano Lc-esi-ms/ms and Data Analysismentioning
confidence: 99%